Kapitalerhaltung bei Anwendung der erfolgsneutralen Stichtagskursmethode zur Währungsumrechnung - Christoph Weber (HfB - Business School of Finance & Management, 2005)
Different methods for the translation of financial statements of foreign subsidiaries result in different profit contributions in the consolidated financial statements and accordingly to different amounts of capital maintained as measured in the group's reporting currency. The translation methods imply assumptions about the validity of macro-economic equilibria such as the Purchasing Power Parity or the Fisher Effect. A model contrasting central and local capital maintenance is developed under the assumption that the International Fisher Effect is valid. The consumption of capital is analyzed when the closing rate method is used with exchange differences offset against capital. This method is prevalent under the application of the functional method according to IAS 21 and SFAS 52. An empirical analysis shows that the impact on the consolidated financial statements of the DAX 30 companies for fiscal year 2004 is significant. With respect to this evidence accounting measures may be misleading for economic decisions or judgements.
urn:nbn:de:101:1-20080825189
Keywords: M41; 330; Foreign currency translation; capital maintenance; functional method; closing rate method; International Fisher Effect; Purchasing Power Parity